2019
DOI: 10.1016/j.sleep.2019.11.463
|View full text |Cite
|
Sign up to set email alerts
|

Age-stratified sex differences in polysomnographic findings and pharyngeal morphology among children with obstructive sleep apnea

Abstract: Background: Childhood obstructive sleep apnea (OSA) has important implications for growth, learning, behavior, cognition and cardiovascular health as well as snoring and OSA in adulthood. In this study, we elucidated the sex differences in polysomnographic (PSG) findings and pharyngeal radiographic data in pediatric OSA patients.Methods: Sixty three children (age between 3 and 15 years old) with OSA [defined as apnea-hypopnea index (AHI) ≥1/h by polysomnography] were enrolled. Lateral neck radiographs were obt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(17 citation statements)
references
References 5 publications
0
16
0
1
Order By: Relevance
“…[10][11][12][13][14] However, limited studies have examined the effects of age and gender in children with OSA, and these studies have reported inconsistent findings. [15][16][17][18][19][20][21] Don et al 17 discovered that among children with OSA, the OSA severity was greater in the children under 3 years of age. In a study by Chuang et al, 21 OSA severity was not significantly different among preschoolers, school-aged children, and adolescents.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12][13][14] However, limited studies have examined the effects of age and gender in children with OSA, and these studies have reported inconsistent findings. [15][16][17][18][19][20][21] Don et al 17 discovered that among children with OSA, the OSA severity was greater in the children under 3 years of age. In a study by Chuang et al, 21 OSA severity was not significantly different among preschoolers, school-aged children, and adolescents.…”
Section: Introductionmentioning
confidence: 99%
“…Both patients in our study were male and aged over 12 years old. Inoshita et al 21 reported that in the adolescent group (8-15 years) the male airway is narrower and the adenoid/nasopharyngeal ratio is greater than that of female adolescents. It is also suspected because of the role of estrogen in the adenoid-tonsil tissue regression in puberty of female patients, whereas not so in male.…”
Section: Discussionmentioning
confidence: 99%
“…This could be possibly attributed to the small sample as well as the onset of OSAS in childhood. Gender differences in the prevalence of OSAS occur from adolescence and henceforth, due to mainly anatomical differentiations in the UA 39 , whereas during childhood, boys and girls demonstrate similar OSAS severity, indicating different pathophysiology 40 . In fact, adenotonsillar hypertrophy is the main cause of OSAS in prepubertal children, regardless of the gender 41 .…”
Section: Discussionmentioning
confidence: 99%